2015
DOI: 10.1038/ncomms9855
|View full text |Cite|
|
Sign up to set email alerts
|

Comprehensive analysis of antibody recognition in convalescent humans from highly pathogenic avian influenza H5N1 infection

Abstract: Understanding the mechanism of protective antibody recognition against highly pathogenic avian influenza A virus H5N1 in humans is critical for the development of effective therapies and vaccines. Here we report the crystal structure of three H5-specific human monoclonal antibodies bound to the globular head of hemagglutinin (HA) with distinct epitope specificities, neutralization potencies and breadth. A structural and functional analysis of these epitopes combined with those reported elsewhere identifies fou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
62
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 38 publications
(62 citation statements)
references
References 62 publications
(121 reference statements)
0
62
0
Order By: Relevance
“…27 The key residues of these neutralization epitopes, as well as the AVFluIgG01 neutralization epitope, were mapped by various mutagenesis assays, such as indirect immunofluorescence assay, yeast surface display and PN assay.…”
Section: Comparison Of Amino Acid Conservation Of Neutralization Epitmentioning
confidence: 99%
“…27 The key residues of these neutralization epitopes, as well as the AVFluIgG01 neutralization epitope, were mapped by various mutagenesis assays, such as indirect immunofluorescence assay, yeast surface display and PN assay.…”
Section: Comparison Of Amino Acid Conservation Of Neutralization Epitmentioning
confidence: 99%
“…The two pan-H5 Abs that we studied, 65C6 and 100F4, recognize two conformational epitopes in the globular head region but outside the RBS (26,27,30). Since we previously showed that SZ06, SX06, and NE14 pseudotypes exhibit different neutralization sensitivities to 65C6 and 100F4 in vitro (26,39), testing Abs 65C6 and 100F4 with these H5 strains would allow us to determine whether Fc-Fc␥R interactions are required for in vivo protection against different individual virus strains.…”
Section: Discussionmentioning
confidence: 99%
“…The 100F4 epitope is located away from the RBS, while the 65C6 epitope is close in proximity to it. Also, binding of 65C6 to its epitope might slightly hinder the engagement of HA to sialic acid (SA) receptors (30). This may explain why Ab 65C6 exhibits low but measureable inhibition of virus attachment, but Ab 100F4 does not (27).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Most of the characterized mAbs against HA from H5N1 virus recognize the epitopes localized in the globular head of HA, most of them overlap the RBS and are isolate-specific, (e.g. Cao et al, 2012b;Du et al, 2013;Wu et al, 2014), while antibodies binding to the stem region have often a broad activity (Tan et al, 2015;Zuo et al, 2015). Extensive review of H5 HA antigenic sites was provided by (Velkov et al, 2013) who described the anti-HA antibodies divided into 3 groups: (i) RBS selective, (ii) non-RBS, membrane-distal globular domain selective and (iii) HA2 selective.…”
Section: Introductionmentioning
confidence: 99%